Controlling of Differential Resistance of p–n-Junctions of Bipolar Transistor in Active Mode by Method of Impedance Spectroscopy - N. I. Gorbachuk; N. A. Poklonski; Ya. N. Marochkina; S. V. Shpakovski (Приборы и методы измерений)
Controlling of parameters of manufactured transistors and interoperational controlling during their production are necessary conditions for production of competitive products of electronic industry. Traditionally for controlling of bipolar transistors the direct current measurements and registration of capacity-voltage characteristics are used. Carrying out measurements on alternating current in a wide interval of frequencies (20 Hz–30 MHz) will allow to obtain additional information on parameters of bipolar transistors. The purpose of the work is to show the possibilities of the method of impedance spectroscopy for controlling of differential resistance of p–n-junctions of the bipolar p–n–p-transistor in active mode.The KT814G p–n–p-transistor manufactured by JSC “INTEGRAL” was studied by the method of impedance spectroscopy. The values of differential electrical resistance and capacitance for base–emitter and base–collector p–n-junctions are defi at direct currents in base from 0.8 to 46 µA.The results of the work can be applied to elaboration of techniques of fi checking of discrete bipolar semiconductor devices.